Catalases of Aspergillus fumigatus - Paris, Sophie (American Society for Microbiology, 2003)
Upon infection of a host, the pathogenic fungus Aspergillus fumigatus is attacked by the reactive oxygen species produced by phagocytic cells. Detoxification of hydrogen peroxide by catalases was proposed as a way to overcome this host response. A. fumigatus produces three active catalases; one is produced by conidia, and two are produced by mycelia. The mycelial catalase Cat1p was studied previously. Here we characterized the two other catalases, their genes, and the phenotypes of gene-disrupted mutants. CatAp, a spore-specific monofunctional catalase, is resistant to heat, metal ions, and detergent. This enzyme is a dimeric protein with 84.5-kDa subunits. The 749-amino-acid polypeptide exhibits high levels of similarity to the Aspergillus nidulans CatA catalase and to bacterial catalase HPII of Escherichia coli. In spite of increased sensitivity to H(2)O(2), killing of ΔcatA conidia by alveolar macrophages and virulence in animals were similar to the killing of conidia by alveolar macrophages and virulence in animals observed for the wild type. In contrast to the Cat1p and CatAp catalases, the mycelial Cat2p enzyme is a bifunctional catalase-peroxidase and is sensitive to heat, metal ions, and detergent. This enzyme, an 82-kDa monomer, is homologous to catalase-peroxidases of several fungi and bacteria. Surprisingly, mycelium of the double Δcat1Δcat2 mutant with no catalase activity exhibited only slightly increased sensitivity to H(2)O(2) and was as sensitive to killing by polymorphonuclear neutrophils as mycelium of the wild-type strain. However, this mutant exhibited delayed infection in the rat model of aspergillosis compared to infection by the wild-type strain. These results indicate that conidial catalase is not a virulence factor and that mycelial catalases transiently protect the fungus from the host.